Consideraç\~oes sobre o financiamento da previdência social - Rogério Nagamine Costanzi; Mário Magalh\~aes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The 2019 pension reform was the most extensive reformulation of the Brazilian pension system since the promulgation of the Constitution of 1988. Despite important changes, such as the gradual end of housing by contribution time in the area of the General Social Security Regime (RGPS) and other important alterations, certainly there still remain challenges and problems for the future of pension system in Brazil. An aspect that needs to be debated in depth is the financing of social security in view of the process of rapid and intense population growth, low economic growth that has characterized the Brazilian economy since the 1980s, the expansion of the Individual Microentrepreneur (MEI) and digital platform workers, among other relevant aspects. This study aims to make generic considerations about the financing of pension system and an analysis of the international pattern considering countries in the Americas and Europe, in addition to references to the brazilian case.
Keywords: H55; 330; pension financing; payroll contribution